2020
DOI: 10.1001/jamapsychiatry.2019.4910
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Psychosis Subgroups With Prognostic Validation and Exploration of Genetic Underpinnings

Abstract: Identifying psychosis subgroups could improve clinical and research precision. Research has focused on symptom subgroups, but there is a need to consider a broader clinical spectrum, disentangle illness trajectories, and investigate genetic associations. OBJECTIVE To detect psychosis subgroups using data-driven methods and examine their illness courses over 1.5 years and polygenic scores for schizophrenia, bipolar disorder, major depression disorder, and educational achievement. DESIGN, SETTING, AND PARTICIPAN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 68 publications
5
41
0
Order By: Relevance
“…A transdiagnostic study identified a cluster containing mainly healthy controls and exhibiting the lowest symptom scores in the observed dimensions [34], likely corresponding to our cluster 0. Our highly impaired cluster 4, with its high percentage of schizophrenic patients, low functioning, and significantly lower EA PGS, may correspond to the severe psychosis subtype from a previous study [32]. Moreover, a single-disorder subtyping study [5] detected five clusters of MDD exhibiting different symptom severities, with one subtype showing an absence of many symptoms, similar to our cluster 0.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…A transdiagnostic study identified a cluster containing mainly healthy controls and exhibiting the lowest symptom scores in the observed dimensions [34], likely corresponding to our cluster 0. Our highly impaired cluster 4, with its high percentage of schizophrenic patients, low functioning, and significantly lower EA PGS, may correspond to the severe psychosis subtype from a previous study [32]. Moreover, a single-disorder subtyping study [5] detected five clusters of MDD exhibiting different symptom severities, with one subtype showing an absence of many symptoms, similar to our cluster 0.…”
Section: Discussionsupporting
confidence: 85%
“…Transdiagnostic clustering supports the existence of diagnostically mixed subtypes across two [4, 2931] or more disorders [3235]. However, previous transdiagnostic clustering studies were limited by small samples and analyzed few disorders or variables [36, 37].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, acute versus chronic mifepristone treatment would impact non-genomic versus genomic GR signaling (respectively), likely representing differential mechanisms of action [ 38 ]. It should also be noted that mifepristone has demonstrated clinical efficacy in patients suffering from psychotic depression (reviewed in [ 39 ]). As such, to detect beneficial effects of mifepristone, future studies may involve chronic treatment regimens prior to behavioral assessments, as well as additional measures of negative affect.…”
Section: Discussionmentioning
confidence: 99%
“…These studies will be important to determine whether observed subgroups represent biologically meaningful, ‘natural kinds’ of groupings, 57 or instead represent segments of a neurocognitive continuum distributed throughout the population. Moreover, future studies should utilise machine-learning approaches to better select variables to be used in clustering algorithms (for example Dwyer et al 58 ), and to broaden outcome variables to model relationships between data-driven subgroups and other clinical and functional outcomes (for example clinical stage transition, admission to hospital), which may assist in planning of personalised interventions. 59…”
Section: Discussionmentioning
confidence: 99%